2020
DOI: 10.1016/j.applthermaleng.2020.115883
|View full text |Cite
|
Sign up to set email alerts
|

Modelling and Co-simulation of hybrid vehicles: A thermal management perspective

Abstract: This is a repository copy of Modelling and co-simulation of hybrid vehicles : a thermal management perspective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 134 publications
0
22
0
Order By: Relevance
“…Yaun et al 24 propose a literature review comparing the environmental and energetic performance of the powertrains on the road vehicles. They bring into discussion the subject of CO 2 mitigation, oil independence, energetic efficiency, powertrain configurations, and storage systems architectures.…”
Section: Overview Of Main Concepts and Technologiesmentioning
confidence: 99%
“…Yaun et al 24 propose a literature review comparing the environmental and energetic performance of the powertrains on the road vehicles. They bring into discussion the subject of CO 2 mitigation, oil independence, energetic efficiency, powertrain configurations, and storage systems architectures.…”
Section: Overview Of Main Concepts and Technologiesmentioning
confidence: 99%
“…The algorithm of the sequential emergency braking and the simulation control subsystem were implemented in this module, by defining such parameters as the maximum speed of the set, force vectors, and moments defined in the model, and by setting the parameters of the emergency braking algorithm. Defining the input and output signals of each of these modules enabled their connection and use of the co-simulation to simulate the emergency braking of a suspended monorail from the given speed, with different settings of the braking algorithm parameters [13,27,[30][31][32][33]. The structure of the computational model and the signal flow, are presented in Figure 2.…”
Section: Computational Model and Its Validationmentioning
confidence: 99%
“…Thermal management of electrified vehicles is widely discussed in the literature. Several review papers can be found addressing the problem of the thermal management for vehicle subsystems [4][5][6][7][8] with special reference to batteries [9][10][11][12][13][14][15][16][17][18][19][20][21][22], for the whole vehicle [23][24][25] or from a modeling perspective [26,27]. The present review aims to provide the designer of the thermal management system the most relevant information about the components, while focusing on the system.…”
Section: Introductionmentioning
confidence: 99%